6 - « Les idoles du temps présent »: nouveaux « paradigmes »et imaginaires de la réussite sociale chez les jeunes citadins au Cameroun - Manga, Jean-Marcellin (Africa Development, 2021)
This paper is a reflection on the figureheads of success which, since the first half of the 1990s in Cameroon, have appeared to be indicative of social promotion in the imaginations of youths. Direct observations and interviews were conducted to collect information. Findings indicate that youths, mostly trapped in a situation in which they were parachuted by a multidimensional crisis, affiliate themselves to accumulation archetypes, thus breaking away, in some instances, with classical references. The paradigms they mostly adhere to are mainly those relating to fun and easy profits as they are considered by youths as likely to enable them to occupy upper rungs on the Cameroonian social ladder.